Information And Communication Technology Strategy Of The Cooperative And Sme Trade Office In Empowering Small And Medium-Sized Enterprises Based On Sharia And Islamic Education In East Aceh District - Baihaki, Baihaki; Kholil, Syukur; Khatibah, Khatibah (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
This research aims to analyze and explain the information and communication technology strategy of the Department of Trade, Cooperatives and SMEs in empowering micro, small and medium enterprises based on Islamic and sharia education in East Aceh Regency. This research method is qualitative-descriptive which is applied with a phenomenological approach. Based on the research results, researchers found that the use of communication technology by the East Aceh Regency Cooperative and SME Trade Service through the use of web pages as a means of communication and information, shows their commitment to facing the challenges of the digital era as well as showing efforts to encourage the development of sharia-based Islamic education. In an effort to optimize the empowerment of Micro, Small and Medium Enterprises (SMEs) in East Aceh Regency, the Cooperative and SME Trade Service has formulated a strategy that includes providing the latest information through communication technology, especially through website pages tailored for SMEs. This strategy not only emphasizes conveying information, but also ensures direct involvement of SMEs in the process, so that they can easily access empowerment programs that are relevant to their needs and interests.